Long-term and short-term interest rates in the United Kingdom - Paish, F. W. (Manchester : Manchester U. P., 1966)
A Modification of the Keynesian theory of interest rate including the relationship between long term and short term interest rate, and the causes of investors expectation.
Includes bibliographical references: p. 53.
ucj, 15/01/2019
Loans
Keywords: Interest rates; Interest; United Kingdom